The Impact of Profitability, Liquidity, Leverage, and Eco-Efficiency on Firm Value in Energy Companies - Asril, Roy Afrizon; Hartanto, Ambar Puji (Universitas Mercu Buana, 2025)
This study aims to analyze the effect of profitability, liquidity, leverage, and eco-efficiency on firm value in energy sector companies listed on the Indonesia Stock Exchange during the 2020–2023 period. The population consists of all energy companies listed on the exchange, with a total sample of 29 firms selected using purposive sampling based on specific criteria. Secondary data were obtained from financial reports published on the official IDX website and the respective companies' websites. The data were analyzed using descriptive statistics and multiple regression analysis. The findings reveal that profitability, as measured by return on equity (ROE), has a positive and significant effect on firm value. In contrast, liquidity (current ratio/CR) shows a negative but statistically insignificant effect, while leverage (debt-to-equity ratio/DER) and eco-efficiency both exhibit positive but insignificant effects on firm value throughout the observation period.